LO SAGRADO EN LA MENTALIDAD DE LA SOCIEDAD MODERNA: ASPECTO FILOSOFICO Y PEDAGOGICO - Domnin,; Groshev,; Filippov,; Antipov, (Revista Inclusiones, 2018)
The article is devoted to the phenomenon of the sacred and its perspective in modern society’s mentality. The authors raise the problem of the dominance of material and technical values over spiritual ones in modern society. It is further stated that the sacred plays an important role in religion and approaches to its interpretation are considered. Attention is paid to the role of the numinous in Orthodox pedagogy. The authors’ understanding of the essence of the sacred is deduced. The problem of the sacralization of the Internet as a manifestation of the inversion of the sacred is considered.